Work-related stress among primary healthcare workers - Ilić, Radovan; Popović, Jovana; Marković, Vladan; Nemec, Vesna; Milošević, Miloš (Vojnosanitetski pregled, 2020)
Background/Aim. There are data on an increased stress level in primary health care workers. The aim of this paper was to investigate the state of stress among employees in the field of primary health care in order to identify the factors that most affect stress and groups that are particularly susceptible to stress. Methods. The study was conducted using a sample of 95 health care workers in the field of primary health care. Data were collected through an anonymous survey consisting of two parts. The first part of the survey included questions related to the characteristics of the workplace and professional and socio-demographic characteristics of the employees. The second part of the survey was based on the Behavioral Health Concepts (BHC) stress test, which is used to estimate the adaptation to stress across four dimensions: overall assessment, quality of life assessment, symptomatology, and level of functioning. Results. Although the total number of respondents fell under the group of moderate stress (mean = 3.97), using descriptive statistical analysis, it was discovered that, 4.2% of the respondents had an increased level of stress. The variance analysis demonstrated that there were statistically significant differences (p < 0.00) between the effects of educational variables (F = 11.68), workplace (F = 14.07) and work time (F = 9.16) on overall stress. Significant interaction between variables workplace and work time was also found [F (2.72) = 3.22; p < 0.046]. Conclusion. Primary health care employees have an increased level of stress, which depends on both the working conditions and the personal characteristics of the employees.